Effectiveness of clinical virtual simulation on knowledge retention, self-directed learning ability and learning effect among nursing students in Xi’an Fanyi university, China - Nan, Han (2024)
With the rapid development of information teaching, clinical virtual simulation has been widely used as a new teaching method in nursing teaching. However, in-depth longitudinal research on self-directed learning ability and knowledge retention is lacking. This study aims to identify the effect of clinical virtual simulation on knowledge retention, self-directed learning ability and the learning effect among nursing students. This work is a quasi-experimental study that was conducted in two months, from October to November 2023. Sophomore nursing students from Xi'an Fanyi University were randomly divided into two groups: the control group (n=43), in which the traditional teaching method was used, and an experimental group (n=41), in which a combination of traditional teaching and clinical virtual simulation was employed. The students in the control group attended a theoretical course, followed by clinical practice courses, and received practice guidance in a laboratory. The students in the experimental group attended a theoretical course, learned and practiced the simulation project on a virtual simulation platform, and then attended clinical practice courses and received practice guidance in a laboratory. The knowledge retention of the students was assessed immediately, two weeks, and one month after the intervention using a multiple-choice test. The self-rating scale of the self-directed learning ability questionnaire was used to determine the self-directed learning ability of the students.